Impact of Artificial Intelligence on Management Education - Raghuvaran A P, M. Annapoorni (Journal of Informatics Education and Research, 2024)
Artificial Intelligence is shifting the authenticity of the management field, in a swift way, due to the advantage of civilizing and reshaping the actual outlook of the target audience of this area. Over the years management has been altered appreciably by replacing the work done by paper and pencil, first with computers, but more prominently with programmes which are able to diminish time expend on recurring work thus trimming down the number of errors. The interest on Artificial Intelligence solutions in this domain is not new-fangled, but based on the last year’s researches, and hence paying more attention to it. Despite the substantial progress there seems to be insufficient data to support companies’ motivation for implanting Artificial Intelligence solutions into their secretarial activities. Also, an important aspect of this authenticity is the competence of experts to acclimatize faster to the new status quo and to attain the compulsory skills to be able to work with reproduction brainpower solutions and to defeat the fear of losing their jobs. This paper focuses on accepting the impact of Artificial Intelligence in management education, by conducting qualitative research based on applicable literature review, of the last few years. This paper highlights the potential changes Artificial Intelligence can bring to the management education, and job scenario, and the necessary steps to be taken in order to prepare for new jobs, in which Artificial Intelligence solutions will be more in attendance.